PENGARUH KONSEP DIRI TERHADAP PRILAKU ASERTIF MAHASISWA STKIP BUDI DAYA BINJAI - Deva Friani Nurul Hasanah (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
Assertive behavior is an ability to communicate what they want, feel, and think to others while maintaining and respecting the rights and feelings other people. the concept of self is something in yourself that people have about themselves in shape with confidence, persaan or attitude of a person through the experiences he gained from interaction with the environment. A positive self concept will bring a person to be assertive, so that when interacting with a positive environmental and insightful it will form a positive self-concept, and vice versa. This type of research is quantitative research. This study aims to determine how big the influence of self-concept toward assertive behavior STKIP Raising student Binjai. The problem in this research are: 1). Is there any influence on the behavior of self-concept of students STKIP Cultivation asrtif Binjai ?. This Penelitain use of hypothesis testing. The population in this study were students smester 5 totaling 250 people. Samples taken as many as 20% of the population, as many as 50 people. Data retrieved through a questionnaire of self-concept and assertive behavior, as many as 80 items before the trial and after the trial 67 items. Data analysis using test engineering requirements analysis, and hypothesis testing ANOVA one way. Based on the research that has been done, the conclusion: there is the influence mkionsep themselves against the assertive behavior STKIP Raising student Binjai. Gasil coefficient of 0.002 P-value is greater than the significance level of 0.05, when the P-valuevlue less than 0.05then declared to have significance. So the results of the analysis ofcoefficient the P-vlue smaller than it otherwise there is a significant level of self-concept influences on behavior influence of student assertive STKIP Cultivation Binjai. Suggestions for further research to be researched and developed with the same topic, is expected to make a more specific measurement tools and simpler language so easy to understand students. In addition to improving the correlation between the factors of each instrument of research, may be created or designed a better measuring devices.